Experience of a National Campaign for Hand Trauma Prevention in France - Bellemere, P.; Guimberteau, J. C. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2013)
In France, hand injuries are the number one cause of all accidents referred to our hospital casualty departments. Their human and economic consequences are very serious. Two thirds of these accidents arise during everyday living activities and a third of them happen at work. The specific prevention of hand injuries in each of these domains has not been sufficiently developed. The authors present the national prevention campaign recently set up by the FESUM.The campaign took place in the form of events held in different towns in France. Each event, lasting from a minimum of 2 days to 10 days maximum, included press conferences, prevention workshops specific to hand injuries, theatrical animation for youngsters, conferences for the general public, meetings in industrial or training college environments, photography and video exhibitions, and the publication of pamphlets and posters. These manifestations were carried out in partnership with the association APAVC and the voluntary involvement of surgeons from the FESUM hand centres in each town visited.Over a period of 2 years, 22 large or medium-sized towns were able to hold these campaign events. By this means, thousands of people – adults, schoolchildren or young, professional apprentices – were made aware of hand injuries and how to prevent them. We were able to reinforce the broadcasting of simple prevention messages launched by the campaign, particularly with regard to wearing gloves for all manual activities, with the help of heavy local, regional and national media coverage.This campaign was the first widespread action of its kind, aimed specifically at the prevention of hand injuries. Furthermore, it was a way of strengthening the credibility of the FESUM hand emergency centres with the health authorities and to promote the services available to patients.
Keywords: prevention; hand; injury; trauma